LncRNA MALAT1 Promotes Tumor Angiogenesis by Regulating MicroRNA-150-5p/VEGFA Signaling in Osteosarcoma: In-Vitro and In-Vivo Analyses - Vimalraj, Selvaraj; Subramanian, Raghunandhakumar; Dhanasekaran, Anuradha (Frontiers in Oncology, 2021)
The present study aims to analyze the expression of long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in human osteosarcoma (OS) cells and to investigate its role in OS-induced angiogenesis. MALAT1 expression in OS cells was significantly higher than in normal osteoblasts. The functional analysis indicated that MALAT1 appears to enhance OS-induced angiogenesis, in vitro and in vivo analyses, endothelial cell proliferation and migration, chick embryo angiogenesis assay, and zebrafish xenograft model. Mechanistically, silencing MALAT1 downregulated vascular endothelial growth factor A (VEGFA) expression and upregulated miR-150-5p expression in OS cells, and MALAT1-mediated angiogenic induction by VEGFA in OS microenvironment. Moreover, MALAT1 directly targeted miR-150-5p and miR-150-5p directly target VEGFA in OS. Overexpression of miR-150-5p downregulates VEGFA expression in OS. More notably, we showed that MALAT1 induced angiogenesis in OS microenvironment by upregulating the expression of VEGFA via targeting miR-150-5p. Overall, our findings suggest that MALAT1 promotes angiogenesis by regulating the miR-150-5p/VEGFA signaling in OS microenvironment. The findings of the molecular mechanisms of MALAT1 in tumor angiogenesis offer a new viewpoint on OS treatment.